Complex airway reconstruction in children with tracheobronchial injuries: a case series. Issue 3 (March 2022) - Salami, Mudasiru A; Beeman, Arun; Ramaswamy, Madhavan; Muthialu, Nagarajan
Paediatric airway surgery in the setting of complex tracheobronchial defects is challenging. This report describes the surgical management and outcomes of pericardial flap repair in three children. The first patient was a 4-month-old boy with a history of tracheoesophageal fistula repair who presented after out-of-hospital cardiac arrest. He was treated by re-do tracheobronchial reconstruction of the carina using a pedicled pericardial flap. The second patient was an 11-month-old boy who presented following aspiration of a button battery. Bronchoscopy showed erosion of the battery through both main bronchi and the oesophagus. The patient underwent emergency reconstruction of the extensive tracheobronchial defect with pedicled right and left pericardial patches. The third patient was a 5-year-old girl who fell from a swing, resulting in avulsion of the right main bronchus. Pedicled pericardium was used to reconstruct the damaged posterior tracheal wall and the right and left main bronchi. All three patients underwent successful repair of complex tracheobronchial defects with good outcomes in terms of survival and quality of life during 6 to 21 months of follow-up. Pedicled pericardial flap repair may be a viable option for achieving improved results in children with severe tracheobronchial defects.